Antibodies against MYC-Associated Zinc Finger Protein: An Independent Marker in Acute Coronary Syndrome? - Ernst, Diana; Widera, Christian; Baerlecken, Niklas T.; Schlumberger, Wolfgang; Daehnrich, Cornelia; Schmidt, Reinhold E.; Gabrysch, Katja; Wallentin, Lars; Witte, Torsten (Frontiers in Immunology, 2017)
IIntroduction: Atherosclerosis is considered the pathophysiology underlying cardiovascular (CVD), cerebrovascular and peripheral vascular diseases. Evidence supporting an autoimmune component is emerging, with imaging studies correlating MYC-associated zinc finger protein antibody (MAZ-Ab) optical density with plaque activity. This study compares MAZ-Ab optical density on ELISA testing among patients presenting with acute coronary syndromes to healthy controls, and investigates the association of MAZ-Ab to traditional CVD risk factors. Methods: Patients admitted with acute coronary syndromes (ACS) between August 2007 and July 2011 were included. Serum samples, taken at presentation were retrospectively tested for MAZ-Ab and compared to serum from healthy volunteers with no CVD risk factors. Large-scale assessment of post-ACS prognostic relevance was performed using the established PLATO cohort. Results: In total 174 ACS patients and 96 controls were included. Among ACS-patients, median MAZ-Ab optical density was higher compared to controls (0.46 vs. 0.27; p=0.001). Although the majority of ACS patients (116/174; 67%) had suffered from a ST elevation myocardial infarction, no significant differences in MAZ-Ab titres were evident between ACS sub-types (p=0.682). No associations between MAZ-Ab optical density and conventional CVD risk factors were identified. Large-scale testing revealed no prognostic stratification regarding re-infarction (OR 1.04 [95%CI: 0.94-1.16]; p= 0.436). Conclusion: MAZ-Ab optical density was higher or all ACS phenotypes compared to controls. Given current understanding of MAZ-Ab function, these findings support an autoimmune component to CVD independent of conventional risk factors and indeed the extent of end-organ damage.